The prevalence of myofascial trigger points in hip and thigh areas in anterior knee pain patients. Issue 1 (January 2020) - Rozenfeld, Evgeni; Finestone, Aharon S.; Moran, Uria; Damri, Elad; Kalichman, Leonid
Abstract: Background: Anterior knee pain (AKP) is a widespread problem among young athletes and soldiers. There are many theories on the etiology of AKP but there is little reference to myofascial trigger points (MTrPs) as a possible contributor. Aim: To evaluate the association between AKP and prevalence of active and latent MTrPs in the hip and thigh muscles in soldiers. Methods: A cross-sectional study was conducted in the Beer-Sheva military outpatient physical therapy clinic. Subjects were 42 men and 23 women referred for physical therapy, 33 with a diagnosis of AKP (cases) and 32 with upper limb complaints (without AKP, controls). All subjects underwent physical evaluation by an examiner blinded to their identity and medical condition. The following muscles were assessed bilaterally for active or latent MTrPs: rectus femoris (proximal), vastus medialis (middle and distal), vastus lateralis (middle and distal) and gluteus medius (anterior, posterior and distal). Results: In six out of eight areas, the cases had a higher prevalence of total active and latent MTrPs than the controls. When summarizing MTrPs by muscle, cases had significantly more MTrPs than controls in each muscle. The largest difference was found in vastus medialis and vastus lateralis; nearly half of the cases had MTrPs in these muscles. Conclusions: Subjects with AKP have a greater prevalence of MTrPs in their hip and thigh muscles than controls, indicating an association between MTrPs and AKP. Further research is necessary to determine whether MTrPs are the cause or the consequence of AKP.